Deteksi dan Tatalaksana Interaksi Obat-Herbal serta Obat-Pangan melalui Anamnesis Farmasi Terstruktur: Suatu Tinjauan Naratif: Suatu Tinjauan Naratif - Gulsyaniraz Qadhi Zakka; Julia Totong (UIMA Press, 2025)
This narrative review evaluates the urgency of herbal and conventional medicine integration in Indonesia, which poses risks of adverse clinical interactions. The review reveals that these interactions involve complex mechanisms capable of reducing efficacy or triggering serious toxicities, such as rhabdomyolysis and bleeding risks. The primary challenge lies in low voluntary patient disclosure and a lack of product quality standardization. As a technical solution, this review asserts that structured pharmacy anamnesis is an effective proactive methodology for early risk detection. Through systematic medication history assessment and the utilization of digital information systems, pharmacists can precisely mitigate therapeutic failures. In conclusion, enhancing therapeutic communication through shared decision-making and interprofessional collaboration serves as the primary foundation for ensuring patient safety. This approach offers a practical framework for clinicians to manage medication complexity within a heterogeneous national healthcare system.